Pendampingan Guru PAUD Brubuh 02 dalam Penanaman Budaya Sadar Lingkungan Sejak Dini - Susilowati, Ida; Trisnani, Asif; Rooiqoh, Qotrunnada Fajr; Rokhaniyah, Hesti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2025)
Purpose: This program aims to create a culture of environmental awareness from an early age in response to environmental issues that impact human security, such as global warming and climate change. Methodology/approach: This service applies discussion, FGD, and enrichment methods, as well as practicum with a character-building approach. Measuring indicators of program success is carried out through pre-test, post-test, and assessment from the affective and psychomotor side. Results/findings: Clustering of partner problems in the fields of knowledge and skills, then developing activity steps in the form of: a. Program socialization, b. FGD related to partner problems, c. Discussion of solutions offered; d Implementation of environmental awareness culture mentoring programs from an early age; e Program enrichment through innovative learning media in the form of thematic books and practice outside the classroom; and f. Monitoring and evaluating service programs, and optimizing service targets. Conclusions: Creativity in learning methods and innovation in learning media are needed to create a culture of environmental awareness from an early age as an effort to realize environmental security based on the 13th and 15th SDG. Limitations: Environmentally conscious cultural activities are only focused on young children, especially TK/PAUD Dharma Wanita Brubuh 02. Contribution: Creating innovative learning media about environmental conservation according to the age of students to increase awareness of young children about the importance of protecting and preserving the surrounding environment in an effort to realize the 13th SDG (Climate Action) and the 15th SDG (life on earth).